A randomized controlled trial on the effect of dietary guidance on the treatment of Henoch-Schonlein purpura in children. (December 2021) - Wang, Li; Yin, Chunyan; Zhang, Meizhen; Mao, Hua; Hao, Huixiang; Hu, Xiaoting; Xue, Wanli
The amino acid-based formulae were extensively added to diet of children for the treatment of Henoch-Schonlein purpura (HSP), and the nutrition and growth situation of children were evaluated after giving new dietary intervention. Patients were randomly divided into restricted diet group (n=30) and dietary guidance group (n=30). Besides, 30 cases with bronchiolitis who had normal diet were selected as the control group. The dietary questionnaire was designed to record the types and intakes of various foods taken by children every day, and the intake levels of nutrients were analyzed. Physical examination, biochemical analysis of blood and urine routine were carried out to evaluate the effect of dietary guidance on their growth and development. The results showed that restricted diet group had lower levels of nutrient intake and the actual/recommended percentage. However, overall nutrient intake level of the dietary guidance group was higher, basically equal to the recommended intake level. Besides, the actual intake and actual/recommended percentage of nutrients of dietary guidance group were significantly higher than those of restricted diet group (p<0.05). Dietary guidance can improve nutrients and protein intake of children with HSP, and reduce the relapse of rash and incidence of complications.